2011
DOI: 10.1128/mcb.05523-11
|View full text |Cite
|
Sign up to set email alerts
|

Cdc25A Regulates Matrix Metalloprotease 1 through Foxo1 and Mediates Metastasis of Breast Cancer Cells

Abstract: Cdc25A is a cell cycle-activating phosphatase, and its overexpression in breast cancers has been shown to correlate with poor prognosis. Most recent studies related to Cdc25A and tumor progression have focused on its role in regulating cell cycle progression. However, less is known about how Cdc25A modulates the metastasis of breast cancer cells. In this study, we revealed that Cdc25A enhances Foxo1 stability by dephosphorylating Cdk2, and Foxo1 was shown to directly regulate transcription of the metastatic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 54 publications
0
50
0
Order By: Relevance
“…Of interest, miR-20a was identified as being overexpressed in the transition from colon mucosa to early adenoma, and was predicted to target multiple WNT pathway genes (Bartley et al 2011). The observation according to which CCAT2-enhanced invasion is mediated by MYC-regulated miRNAs and also possibly by other pro-metastatic targets such as CDC25A (Feng et al 2011), rather than by MYC itself, suggests a complex regulatory network that needs to be further explored in the future. This is also in agreement with the recent observation by The Cancer Genome Atlas (TCGA) Consortium that MYC-driven transcriptional activation and repression play important roles in colon cancer (The Cancer Genome Atlas Network 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, miR-20a was identified as being overexpressed in the transition from colon mucosa to early adenoma, and was predicted to target multiple WNT pathway genes (Bartley et al 2011). The observation according to which CCAT2-enhanced invasion is mediated by MYC-regulated miRNAs and also possibly by other pro-metastatic targets such as CDC25A (Feng et al 2011), rather than by MYC itself, suggests a complex regulatory network that needs to be further explored in the future. This is also in agreement with the recent observation by The Cancer Genome Atlas (TCGA) Consortium that MYC-driven transcriptional activation and repression play important roles in colon cancer (The Cancer Genome Atlas Network 2012).…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, FoxO1 could up-regulate the cell-cycle inhibitors p21 and p27, while down-regulate the cell cycle regulator cyclinD1/2, consequently leading to G1/S cell-cycle arrest [18]. Indeed, FoxO1 expression or activity was reduced in several types of cancers, including gastric cancer, breast cancer and osteosarcoma [19,20,21,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated increased Fox1 activity following CDC25A-indcued dephosphorylation of CDK2. Inhibition of CDC25A inhibits metastases in BC mouse models, suggesting that this phosphatase may be a potential target for advanced stages of the disease (248).CDC25B is overexpressed in primary BC tumours (249), although expression levels do not always correlate with an aggressive phenotype (250).…”
Section: Breast Cancermentioning
confidence: 99%